Ross Sea Benthic Ecosystems: Macro- and Mega-faunal Community Patterns From a Multi-environment Survey - Vonda J. Cummings; David A. Bowden; Matthew H. Pinkerton; N. Jane Halliday; Judi E. Hewitt (Frontiers in Marine Science, 2021)
The Ross Sea, Antarctica, is amongst the least human-impacted marine environments, and the site of the world’s largest Marine Protected Area. We present research on two components of the Ross Sea benthic fauna: mega-epifauna, and macro-infauna, sampled using video and multicore, respectively, on the continental shelf and in previously unsampled habitats on the northern continental slope and abyssal plain. We describe physical habitat characteristics and community composition, in terms of faunal diversity, abundance, and functional traits, and compare similarities within and between habitats. We also examine relationships between faunal distributions and ice cover and productivity, using summaries of satellite-derived data over the decade prior to our sampling. Clear differences in seafloor characteristics and communities were noted between environments. Seafloor substrates were more diverse on the Slope and Abyss, while taxa were generally more diverse on the Shelf. Mega-epifauna were predominantly suspension feeders across the Shelf and Slope, with deposit feeder-grazers found in higher or equal abundances in the Abyss. In contrast, suspension feeders were the least common macro-infaunal feeding type on the Shelf and Slope. Concordance between the mega-epifauna and macro-infauna data suggests that non-destructive video sampling of mega-epifauna can be used to indicate likely composition of macro-infauna, at larger spatial scales, at least. Primary productivity, seabed organic flux, and sea ice concentrations, and their variability over time, were important structuring factors for both community types. This illustrates the importance of better understanding bentho-pelagic coupling and incorporating this in biogeographic and process-distribution models, to enable meaningful predictions of how these ecosystems may be impacted by projected environmental changes. This study has enhanced our understanding of the distributions and functions of seabed habitats and fauna inside and outside the Ross Sea MPA boundaries, expanding the baseline dataset against which the success of the MPA, as well as variability and change in benthic communities can be evaluated longer term.